Stereoselective Oxa‐Michael Addition of Tyrosine to Propargyl Aldehyde/Esters: Formation of Benzofurans and Flavones. Issue 18 (23rd July 2019) - Vasconcelos, Stanley N. S.; de Oliveira, Isadora Maria; Shamim, Anwar; Zukerman‐Schpector, Julio; Pimenta, Daniel C.; Stefani, Hélio A.
Abstract: The steroselective oxa‐Michael addition of the phenol moiety present in tyrosine and 3‐iodotyrosine to different propargyl aldehydes delivered products with predominantly Z stereochemistry, as evidenced by X‐ray crystallography analysis. When ethyl propiolate was used as the propargyl ester source, the products were achieved with exclusively E stereochemistry with yields ranging from 17% to 91%. The oxa‐Michael addition compounds served as substrates in the synthesis of 5‐ and 6‐membered heterocyclic compounds. The atmosphere applied to the reaction medium directly influenced the formation of the products. When an inert atmosphere of nitrogen was applied, a 2‐aryl‐3‐formyl‐5‐alanylbenzofuran core was selectively obtained via a Heck intramolecular reaction, while the reactions carried out under a carbon monoxide atmosphere led exclusively to 6‐alanyl‐2‐arylflavone derivatives via reductive intramolecular acylation. Abstract :